Phosphorus fractions and correlation with soil attributes in a chronosequence of agricultural under no-tillage - Rosset, Jean Sérgio; Guareschi, Roni Fernandes; Pinto, Luiz Alberto Rodrigues da Silva; Pereira, Marcos Gervasio; Lana, Maria do Carmo (Semina: Ciências Agrárias, 2016)
In no-tillage (NT) soils, changes in the quantity and quality of soil organic matter (SOM) have been observed over time. These changes can interfere with the dynamics of P in surface soil layers. Thus, the objectives of this study were: to evaluate the organic and inorganic fractions of P and their degree of lability (labile, moderately labile, and moderately recalcitrant) in an Oxisol under NT for 6 years (NT6), 14 years (NT14), and 22 years (NT22) and cultivated with a succession of soybean and corn/wheat. The fractions were evaluated for 16 years of NT, with the last four years under integrated corn second crop and Brachiaria (NT16+B). We also analyzed an area of native forest, as well as analyzing the correlations between the results of the P fractions of these areas with other attributes such as total carbon content, vegetable waste deposited on the ground, phosphorus and humic fractions remaining in SOM. From each of the areas, samples were collected at 0.00-0.05 m and 0.05-0.10 m. A completely randomized design with 5 replicates was used. Management of phosphorus fertilization and SOM following adoption of the SPD of time (6 to 22 years) increased the levels of all fractions of inorganic P (0.0 to 0.10 m), as well as the fractions of labile (0.05-0.10 m), moderately labile (0.0-0.10 m), and moderately recalcitrant (0.05-0.10 m) organic phosphorus. The correlation matrix shows interactions between the evaluated soil attributes, especially between inorganic phosphorus fractions and fulvic and humic acids and between the moderately recalcitrant organic phosphorus and humin fraction.